An improved hydrodynamic model for percolation and drainage dynamics for household and agricultural waste beds. (October 2019) - Digan, Laura; Horgue, Pierre; Debenest, Gérald; Dubos, Simon; Pommier, Sébastien; Paul, Etienne; Dumas, Claire
Graphical abstract: Highlights: Physical and hydrodynamic characterisation of household wastes beds was performed. An easily calibrated dual-porosity model was proposed and calibrated. The proposed model included a reservoir fraction in macroporosity. The model was validated on household and agricultural wastes. Experimental water retention dynamics were numerically reproduced. Abstract: This study focuses on the hydrodynamic modelling of percolation and drainage cycles in the context of solid-state anaerobic digestion and fermentation (VFA platform) of household solid wastes (HSW) in leach bed reactors. Attention was given to the characterization of the water distribution and hydrodynamic properties of the beds. The experimental procedure enabled the measurement of water content in waste beds at different states of compaction during injection and drainage, and this for two types of HSW and for two other type of wastes. A numerical model, set up with experimental data from water content measurements, highlighted that a capillary-free dual-porosity model was not able to correctly reproduce all the hydrodynamic features and particularly the drainage dynamics. The model was improved by adding a reservoir water fraction to macroporosity which allowed to correctly simulate dynamics. This model, validated with data obtained from agricultural wastes, enabled to explain more precisely the water behaviour during percolation processes and these results should be useful for driving either solid-state anaerobic digestion or fermentation reactors. Indeed, this implies that the recirculation regime will impact the renewal of the immobile water fraction in macroporosity, inducing different concentration levels of fermentation products in the leachate.